The art of movie storyboards visualising the action of the world's greatest films - Halligan, Fionnuala (Ilex Press, 2015)
"The art of movie storyboards celebrates this art, showcasing a vast collection of storyboards in range of styles, and including some of cinema's greatest moments. The collection includes the work of pioneers such as William Cameron Menzies (Gone with the wind) and Saul Bass (Psycho, Spartacus), as well as contemporaries such as Raul Monge (Pan's labyrinth) and Jane Clark (Harry Potter and the goblet of fire). Many are seen here for the first time, and all are accompanied by insights into the films featured, their directors, and, of course, the storyboard artists"--Provided by publisher.